PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM UPAYA PENINGKATAN MINAT BELAJAR MAHASISWA PADA POKOK BAHASAN TEORI GRAF: Indonesia - Surya Adi Putra I Putu; Wardika I Wayan Gede (FPMIPA IKIP PGRI Bali, 2021)
This study aims to examine and describe the increase in learning interest in learning graph theory using the jigsaw type cooperative method at STMIK STIKOM Indonesia. The type of research carried out is classroom action research (CAR) with the Kurt Lewin model. This research was conducted in class J semester 2 of the STMIK STIKOM Indonesia Information Engineering Study Program with 64 students. The consideration of choosing this campus as a research place is because interest in learning mathematics on the subject of graph theory is still lacking and similar research has never been conducted. Based on the results of the study, it can be concluded that learning by applying the jigsaw type of cooperative learning model can increase student interest in learning. This is indicated by the calculation of the interest in learning questionnaire score in the very good category, increasing in the pre-cycle to cycle I by 16.12%, then increasing again in cycle 1 to cycle 2 by 51.61%. , the category of learning interest scores in cycle 2 has met the minimum requirements.